Biostimulatory Action of a Plant-Derived Protein Hydrolysate on Morphological Traits, Photosynthetic Parameters, and Mineral Composition of Two Basil Cultivars Grown Hydroponically under Variable Electrical Conductivity - Michele Ciriello; Luigi Formisano; Christophe El-Nakhel; Giandomenico Corrado; Youssef Rouphael (Horticulturae, 2022)
Hydroponics is a viable alternative to open field cultivation for year-round vegetable production in urban areas. However, the total dependence on external chemical inputs (fertilizers) makes these systems often less environmentally sustainable. In this perspective, the use of biostimulants could represent a valuable and eco-friendly tool to limit the excessive use of fertilizers without a negative impact on the yield. To this end, our work aimed to evaluate the productive and physiological response of two cultivars of ‘Genovese’ basil (Eleonora and Italiano Classico) for the industrial production of “pesto” grown for 22 days in two nutrient solutions with different electrical conductivity (1 and 2 dS m−1) and the application of two doses of protein hydrolysates (0.15- and 0.30-mL L−1 of Trainer® in the nutrient solution). The mineral profile was evaluated by ion chromatography coupled with a conductivity detector, while pigments were evaluated by UV-Vis spectrophotometry. Generally, the nutrient solution concentration did not significantly affect the fresh yield of the two cultivars tested. On the contrary, the use of the maximum dose of biostimulant (BT2 = 0.30 mL L−1 of nutrient solution) increased fresh yield, leaf area, and ACO2 by 20.7, 27.5, and 17.6%, respectively, compared with the control. Using the lowest dose of biostimulant (BT1 = 0.15 mL L−1 of the nutrient solution) reduced nitrate by 6.6% compared with the control. The results obtained showed that basil cultivation in a floating raft system combined with biostimulant in the nutrient solution could be an excellent solution to improve productivity, reduce nitrate, and cut fertilizer costs.